A Critique of Ignored Followers of Charisma in the Book Sociology of National Charisma: The Collapse of Social Structures and the Emergence of Charisma - Fateme Daneshvar Muhammadzadegan; Reza Abedi Gonabad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Sociology of National Charisma is a book by Majid Fouladian that analyzes the collapse of social structures and the rise of national charisma. The author uses a historical structural method to study the structural changes on the eve of the two constitutional revolutions and the Islamic Revolution and concludes that in the Qajar period, the construction of social networks prevented the formation of comprehensive solidarity. Considering such construction, it seemed unlikely the emergence of national charisma, but at the end of the Pahlavi regime, due to the collapse of the traditional structure and the emergence of social crises in a society that had reached a level of national cohesion, and with the emergence of ideology based on society culture, it became possible to form a national society and national charisma. In this article, we intended to review the book The Sociology of National Charisma in the framework of integrated analysis (structure-agent). The results show that Fooladian does not explain the relationship and role of followers in the emergence of charisma. In fact, the author merely explains the structures and their effect on the emergence of charisma, and ignores the agency of charisma followers in the emergence of charisma.